Ethnoveterinary Knowledge and Biological Evaluation of Plants Used for Mitigating Cattle Diseases: A Critical Insight Into the Trends and Patterns in South Africa - Chakale, Mompati V.; Mwanza, Mulunda; Aremu, Adeyemi O. (Frontiers in Veterinary Science, 2021)
Cattle farming is a traditional agricultural system that contribute to the rural sector, social and cultural values of the communities. Cattle as common with other livestock, are affected by many diseases that cause mortality and economic losses. In many rural households, the use of ethnoveterinary medicine plants and associated knowledge are popular for managing cattle diseases especially in areas experiencing challenges with conventional veterinary medicine. Evidence on the documentation of and biological evaluation of plants used against cattle diseases remain understudied and fragmented. The aim of the review is to collate and analyse the ethnoveterinary knowledge and biological evaluation of plants used against cattle diseases in South Africa. Different scientific databases were systematically explored to extract data from 37 studies that were eligible for the review. A total of 310 medicinal plants from 81 families used to treat 10 categories of cattle diseases across seven (7) provinces in South Africa. Leguminosae (Fabaceae), Compositae (Astereceae), Asparagaceae and Xanthorrhoeaceae were the most frequently used plant families. Common plant parts used were leaves and roots. Thirty-seven (37) plants are prescribed as combination remedy. Common preparation methods were infusion and decoction while the administration mode was dominantly oral and topical. In terms of diseases, the most treated ones were general systems infection, reproduction disorders and gastrointestinal problems. Currently, an estimated 21% of the 310 plants have been evaluated for diverse biological activities using relevant bioassays related to cattle diseases. Antibacterial activity remained the most studied biological activity. Evidence from the review revealed the significance of ethnoveterinary medicine against cattle diseases especially in rural areas of South Africa. Nevertheless, the use of plants for cattle diseases among other ethnic groups, particularly in the Northern Cape and Western Cape, remain under-studied.